READING WRITING BY WOMEN - Harry Aveling (Soegijapranata Catholic University, 2006)
Differences in gender may produce differences in style of writing. It is my intension here to show that the style used by female in contrast to male writers results in a number of significant differences. Some of them are caused by the writers cultural background. Being a teacher, I would like to share with others how the gender and feminist theories can be applied to analyze writings by women.